The Implementation of Total Quality Management in Forming Student’s Religious Totality - Qodri, Ahmad; Kusuma, Sri; Warlizasusi, Jumira; Pratama, Surya Adi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Aqidah, sharia and morals are the fundamental aspects in Islamic teachings that need to be totally instilled in oneself. However, the cultivation of those main values, in fact, has not been maximized. This problem also becomes a concern of SMKIT Khoiru Ummah Rejang Lebong Bengkulu in which the cultivation of aqidah, sharia and morals faces the challenges and obstacles. At the same time, such problems indicate that the totality of students in applying Islamic values has not been thoroughly embedded. This facts then require the school to implement Total Quality Management in its religious education activities. Therefore, this article aims to describe the implementation of Total Quality Management as an effort to form the quality and religious totality of students. This type of research is qualitative-descriptive. Data were collected by conducting interviews and observations. The data were then analyzed by reducing, displaying and drawing conclusions. The validity of the data was tested by using triangulation technique. The result of this study shows that the efforts to form religious totality are carried out through routine religious activities at school, giving reprimands, directions, punishments, exemplary, environmental conditioning, school culture and the application of noble values through learning and training. Through these activities, the school applies the principles of Total Quality Management which include evaluation and improvement, optimizing the role of the school headmaster, cooperation, prioritizing customer satisfaction, conducting planned training, and improving quality of learning.